Early recurrence of malignant fibrous histiocytoma of the heart - (:unkn) unknown (Blackwell Publishing Inc., 1996)
Malignant fibrous histiocytoma is a pleomorphic soft tissue sarcoma, which constitutes only 2% of all cardiac malignancies and is typically located in the left atrium. We report a young male patient with malignant fibrous histiocytoma located on the right side of the heart. Early recurrence was observed after extensive surgical resection to relieve symptoms of outflow tract obstruction. Noninvasive evaluation and management with regard to the literature are discussed.
Keywords: malignant fibrous histiocytoma